Chile and international trade with a gender perspective:: historical experience and challenges of the new feminist foreign policy - Ramos Borges, Osnarci Rafael; Vallina, Ana María; Bustos, Scarlett; Vere-Stead, Francisca (Latin American Journal of Trade Policy, 2024)
The study examines the historical evolution of the inclusion of the gender dimension in Chile’s international trade insertion, focusing particularly on the recent Feminist Foreign Policy, which makes it a pioneer in the South American region in adopting one of these characteristics. Problems such as wage inequality, low female representation in decision-making and the lack of effective mechanisms to guarantee gender commitments in trade agreements at the international level are highlighted. In view of this, a review of this new millennium is made to analyze the importance of the most important regional and plurilateral agreements that have guided action in various intergovernmental scenarios and of this new national need to address the structural causes of inequality to consider the specific needs of women and other historically invisible groups in society. It also emphasizes the importance of strengthening the mechanisms for monitoring and evaluating trade policies from a gender perspective, as well as the creation of dispute settlement bodies to ensure compliance with the commitments undertaken to eradicate poverty and promote fairer, more equitable and inclusive growth for all.